Ionic liquids and continuous flow processes: a good marriage to design sustainable processes. Issue 5 (12th May 2015) - García-Verdugo, Eduardo; Altava, Belen; Burguete, M. Isabel; Lozano, Pedro; Luis, S. V.
<x xml:space="preserve">Abstract</x> In the last few years the use of Ionic Liquids (ILs) as alternative solvents for (bio)catalytic processes has increased substantially, and the benefits and different approaches reported to combine continuous flow systems and ILs are at the core of this overview.